2009
DOI: 10.1017/s1355617709090225
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus volume and episodic memory in schizophrenia

Abstract: Previous studies of schizophrenia have suggested a linkage between neuropsychological (NP) deficits and hippocampus abnormality. The relationship between hippocampus volume and NP functioning was investigated in 24 patients with chronic schizophrenia and 24 matched healthy controls. Overall intracranial, white and gray matter, and anterior (AH) and posterior (PH) hippocampus volumes were assessed from magnetic resonance images (MRI). NP domains of IQ, attention, and executive function were also evaluated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 79 publications
(89 reference statements)
3
24
0
Order By: Relevance
“…More specifically, our study revealed that the surface-inward deformation within the anterior hippocampus was associated with cortical thinning in the regions involved in both dorsal and ventral visual processes. The disruption of the hippocampal-cortical connectivity in terms of the disconnectivity strength between the hippocampus and the cortex may underlie cognitive deficits observed in impaired performance on hippocampal-dependent memory tasks (Cirillo and Seidman, 2003;Meyer-Lindenberg et al, 2005;Thoma et al, 2009), reduced functional connectivities involving the hippocampus in resting functional MRI (Zhou et al, 2008), and impaired executive attention and working memory found in functional (Rasser et al, 2005) and structural neuroimaging studies (Bilder et al, 1995;Harrison, 2004;Rasser et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, our study revealed that the surface-inward deformation within the anterior hippocampus was associated with cortical thinning in the regions involved in both dorsal and ventral visual processes. The disruption of the hippocampal-cortical connectivity in terms of the disconnectivity strength between the hippocampus and the cortex may underlie cognitive deficits observed in impaired performance on hippocampal-dependent memory tasks (Cirillo and Seidman, 2003;Meyer-Lindenberg et al, 2005;Thoma et al, 2009), reduced functional connectivities involving the hippocampus in resting functional MRI (Zhou et al, 2008), and impaired executive attention and working memory found in functional (Rasser et al, 2005) and structural neuroimaging studies (Bilder et al, 1995;Harrison, 2004;Rasser et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example McDonald et al, suggests that they have similar white matter deficits but contrasting gray matter deficits (McDonald et al 2005). Although it might be anticipated that altered patterns of symptomatology and indeed psychological, social and occupational functioning should correlate with hippocampus and amygdala structural alterations, evidence of such systematic relationships remains inconsistent (Goldman and Mitchell 2004;Rajarethinam et al 2001;Rosso et al 2007;Suzuki et al 2005;Thoma et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Within these networks the hippocampus, which is located in the medial temporal lobe, is thought to have a prominent role in the onset of different cognitive dysfunctions (Tamminga et al 2010). In schizophrenia patients, and their relatives, a link between hippocampal and temporal lobe volume reduction and declarative memory performance has been found, although some studies have failed to affi rm this relationship (DeLisi et al 1991;Torres et al 1997;Gur et al 2000;Seidman et al 2002;Antonova et al 2004; Thoma et al 2009). …”
Section: Introductionmentioning
confidence: 99%